2015
DOI: 10.1111/2041-210x.12442
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy models for data with false positive and false negative errors and heterogeneity across sites and surveys

Abstract: Summary False positive detections, such as species misidentifications, occur in ecological data, although many models do not account for them. Consequently, these models are expected to generate biased inference. The main challenge in an analysis of data with false positives is to distinguish false positive and false negative processes while modelling realistic levels of heterogeneity in occupancy and detection probabilities without restrictive assumptions about parameter spaces. Building on previous attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…Additional complications could be considered. For example, the assumption that detections classified as certain are never false positives might be violated (Ferguson, Conroy & Hepinstall‐Cymerman ). One could investigate the effect of this violation on optimal design or the effect of more conservative or liberal protocols for classifying detections as certain on the accuracy of model estimates (Miller et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional complications could be considered. For example, the assumption that detections classified as certain are never false positives might be violated (Ferguson, Conroy & Hepinstall‐Cymerman ). One could investigate the effect of this violation on optimal design or the effect of more conservative or liberal protocols for classifying detections as certain on the accuracy of model estimates (Miller et al .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Miller et al . () proposed that surveyors might use two survey methods, one of which generates uncertain detections, while the other only generates certain detections (see Ferguson, Conroy & Hepinstall‐Cymerman for a Bayesian formulation). For example, an acoustic survey might yield uncertain detections (false positives possible) while a capture survey might generate only certain detections (no false positives).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, previous studies have shown, both empirically and with simulations, that even when including some level of certain detections, heterogeneity in detection and false occupancy rates can induce bias in estimates of habitat occupancy (Ferguson et al. , Miller et al. , Banner et al.…”
Section: Discussionmentioning
confidence: 73%
“…However, even when false‐positive detection is included in occupancy models, heterogeneity in true and false detection rates can induce bias in estimates of habitat occupancy (Ferguson et al. , Miller et al. , Banner et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation